Bibliografija kot podlaga za raziskovanje - Kocijan, Gregor (Slavistična revija, 2013)
Preparation of a register, list, or inventory on a topic is the first step ina research project. The Žfield of literary studies examines literary works of individuals, secondary sources, literary periods, genres of literary works, and particular literary components (e.g., chief themes and motifs, literary works' structures, manner of textualization, verse forms and meaning,compositional features, etc.), among other things. Research requires an exact blueprint describing the object of study, which in turn generates a bibliography that ensures a work's comprehensiveness. In addition, a bibliographic list frequently points up things of evolutionary significance, such as intervals between literary works, a concept changing through a writer's works, the rate of recurrence of some phenomenon, and so forth.
Keywords: bibliografija; bibliography; bibliometrics; bibliometrija; Cobiss; COBISS.net; dLib; Slovene literary criticism; Slovene literature; slovenska književnost; slovenska literarna veda